Overexpression of Nrf2 Protects Against Lipopolysaccharide and Cerulein-Induced Pancreatitis In Vitro and In Vivo. Issue 3 (March 2020) - Fu, Xu; Li, Peiwu; Yin, Wen; Ma, Li; Zhang, Bei; Zhen, Lingling; Meng, Yanfei; Han, Li; Wang, Yingzhen
Abstract : Objectives: In this study, we focused on the function of nuclear factor E2–related factor 2 (Nrf2) in acute pancreatitis (AP), which has been shown to have protective effects in gliomas, hepatocytes, and astrocytes. Methods: Acute pancreatitis cell line and animal model were induced by administration of lipopolysaccharide and cerulein into the cell supernatant or intraperitoneal injection. Oxidative stress status was evaluated by measuring the level of amylase, C-reactive protein, malondialdehyde, superoxide dismutase, and myeloperoxidase. Morphological alterations in the pancreas were evaluated by hematoxylin-eosin staining, the wet-to-dry weight ratio, and the pathology injury scores. Western blot, reverse transcription-polymerase chain reaction, and immunofluorescence staining were performed to analyze the expression of Nrf2, Heme oxygenase 1, and NAD(P)H: quinone oxidoreductase 1. Results: Overexpression of Nrf2 inhibits oxidative stress and inflammatory responses by inducting the expression of superoxide dismutase as well as reducing the level of amylase, malondialdehyde, and myeloperoxidase in the AR42J rat pancreatic acinar cells in AP. Importantly, overexpression of Nrf2 displayed the same protective effect in vivo. Data from an AP rat model showed that Nrf2 could relieve pancreatic damage. Conclusions: These results indicated that Nrf2 has a protective role in lipopolysaccharide and cerulein-induced cytotoxicity, providing potential therapeutic strategies for the treatment of AP.